The Effectiveness of the As-Sahlah Textbook in Improving Arabic Language Proficiency among Students of the Faculty of Islamic Economics and Business: Efektivitas Buku Teks As-Sahlah dalam Meningkatkan Kemahiran Bahasa Arab di Kalangan Mahasiswa FEBI - Agus Khamid; Muhandis Azzuhri; Muhammad Ulil Fahmi (Language Development Center, 2026)
Background: Arabic language proficiency is a fundamental requirement for students of Islamic Economics and Business, as it enables access to primary Sharia sources, comprehension of Islamic economic literature, and mastery of professional terminology used in Sharia-based financial and business practices. Purpose: This study aims to investigate the effectiveness of the As-Sahlah textbook in improving the Arabic language proficiency of students at the Faculty of Islamic Economics and Business (FEBI). Method: This research adopted a mixed-methods approach with a sequential explanatory design, in which quantitative data collection and analysis preceded qualitative inquiry. Quantitative data were obtained through pretest–posttest assessments and perception questionnaires administered to 30 FEBI students enrolled in an Arabic for Economics course. The instruments were designed to measure learning outcomes, perceived effectiveness, ease of use, relevance, and learning motivation. Qualitative data were collected through in-depth interviews and classroom observations to capture students’ learning experiences and engagement during the instructional process. Quantitative data were analyzed using descriptive statistics and gain score analysis, while qualitative data were examined using the interactive analysis model of Miles and Huberman, supported by source and method triangulation to ensure credibility. Results and Discussion: The results lead to that the use of the As-Sahlah textbook leads to measurable improvements in students’ Arabic proficiency, particularly in vocabulary mastery and comprehension of Islamic economic texts. Students also reported increased motivation, clearer understanding of Sharia-based business contexts, and greater perceived relevance of Arabic learning to their field of study. This study makes a novel contribution by integrating quantitative learning outcome data with qualitative insights to explain how contextualized materials facilitate learning transfer in Arabic for Specific Purposes. Conclusions and Implications: The study concludes that the use of the As-Sahlah textbook is associated with improvements in students’ Arabic proficiency, as reflected in the increase from a mean pretest score of 79.39 to a mean posttest score of 84.68, resulting in a score gain of 5.29. The findings suggest that context-based Arabic textbooks should be further developed and adopted, and future research should explore digital enrichment and larger samples to strengthen Arabic for Specific Purposes (ASP) pedagogy in Islamic higher education.